Dark skies use in tourism : Good practices examples - Silvennoinen, Daisy; Kupiainen, Tarja; Ruotsalainen, Marja-Liisa (Karelia University of Applied Sciences, 2022)
Demand for tourist activities that use the night sky (“dark skies tourism”) as a resource is growing. The Northern Periphery and Arctic region have vast areas with little or no light pollution, but the dark skies tourmis is still in infancy compared to other areas across the globe, First part of this report presents the state of dark skies tourism and infrastructure in Finland. The main challenges facing the sector are also discussed. Finally, the report presents best dark skies tourism practice examples from across the globe, in an attempt to try to develop detail understanding of current dark-sky tourism practices, their collaborations, attitudes towards approaches, and identification of barriers and opportunities for Northern Periphery and Arctic regions.